2021
DOI: 10.36909/jer.8783
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of tool wear, surface roughness, sound intensity, and power consumption during hard turning of AISI 4140 steel using multilayer-coated carbide inserts

Abstract: The present study investigated the machinability aspects, namely, surface roughness, sound intensity, power consumption, and crater wear, during dry turning of hardened AISI 4140 steel (63 HRC) employing (TiCN/Al2O3/TiN) multilayer-coated carbide inserts under dry cutting condition. The relationship between machining parameters and output parameters was determined using the Taguchi design. The analysis of variance was employed to evaluate the contributions of input parameters on output parameters. The main eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Thus, the temperature distribution can be expressed then in a dimensionless form in terms of the Biot number. Considering that the perimeter 𝑃 multiplied by the length of the fin 𝐿 is equal to the total area of the lateral surface (Şahinoğlu and Rafighi, 2021):…”
Section: Methods and Validation A Introductory Elements On Heat Trans...mentioning
confidence: 99%
“…Thus, the temperature distribution can be expressed then in a dimensionless form in terms of the Biot number. Considering that the perimeter 𝑃 multiplied by the length of the fin 𝐿 is equal to the total area of the lateral surface (Şahinoğlu and Rafighi, 2021):…”
Section: Methods and Validation A Introductory Elements On Heat Trans...mentioning
confidence: 99%
“…From the analysis of table 2 and fig. 6, it can be concluded that TiN carbide insert tools have better wear resistance than TiAlN/Al2O3, this is because the titanium nitride (TiN) coating has lubricating properties that reduce friction between the cutting insert and the workpiece, thereby preventing temperature increases at higher cutting speeds and consequently slowing the growth of tool wear [17].…”
Section: 1mentioning
confidence: 99%
“…17 This material has excellent corrosion resistance, high hardness, high strength, good formability, and good weldability. [18][19][20] Thanks to the amount of carbon in its chemical composition, AISI 4140 steel can reach high hardness through heat treatment. Therefore, AISI 4140 steels are widely used in hard turning processes.…”
Section: Introductionmentioning
confidence: 99%